Foreign tourists and local women: Sex trade and romance in the nights of Iracema Beach in Fortaleza - Aquino, Jania Perla Diógenes de (Revista de Antropologia, 2015)
The article discusses the relations between foreign tourists and native women at Iracema Beach in Fortaleza. The views of residents of the seafront and nearby neighborhoods, whose perception of the "encounters" between "gringos" and local young women are strictly negative, are presented. On the one hand, the women are considered "victims" of the sexual interests of foreigners; on the other hand, they are taken as "guilty" for Fortaleza having become internationally known as a prostitution ring. The text also examines the narratives and perceptions of call girls acting in the nights of Iracema Beach, who emphasize positive experiences afforded by the "gringos", such as drinking and dining in upscale restaurants, gifts, trips abroad and even dating and marrying. Besides highlighting the uncertainty between trade and affection in the sexual and affective exchanges between call girls and “gringos”, the article argues that such relations interfere in the local asymmetries and social inequalities